Modeling the interaction between powder particles and laser heat sources - Baloyi, P.; Desai, D. A.; Arthur, N. K. K.; Pityana, S. L. (Frontiers in Manufacturing Technology, 2024)
This study investigates the spheroidization of titanium Ti-6Al-4V powder particles using numerical models developed in Abaqus and OpenFOAM software, with the objective of transforming irregular particles into spherical ones. Spherical particles are crucial in powder-based additive manufacturing due to their superior flowability, packing density, and mechanical properties, which enhance precision in printing and improve the quality of final products. However, while conventional techniques like gas atomization and plasma spheroidization have been widely researched, the use of laser spheroidization remains underexplored. This study aims to address this gap by conducting detailed numerical analyses of laser spheroidization. Heat transfer from the laser to powder particles was modeled using the transient uncoupled heat transfer method with latent heat considerations, while particle deformation was simulated using a phase-fraction-based interface-capturing approach with Navier-Stokes equations. The results, validated against analytical models, show that particles within the 20-80 μm range undergo optimal spheroidization within a 0.005-second residence time under laser heating. Particles smaller than 30 μm reached evaporation temperatures of 5000°C, while larger particles reshaped without evaporating when exposed to a typical heat flux of 94 MW/m² (1.8 kW laser power). This study demonstrates that laser spheroidization of Ti-6Al-4V can potentially increase powder yield by 10%, offering higher power density and shorter melting times compared to plasma spheroidization, thus presenting a more efficient alternative for specific particle sizes